Listen and Speak: Power-Knowledge-Truth and Cochlear Implants in Toronto - Edelist, Tracey (Disability Studies Quarterly, 2015)
Cochlear implants and auditory-verbal therapy are the latest techniques and technologies used to make deaf people learn to listen and speak. This paper provides a genealogical analysis of the Cochlear Implant Program at SickKids Hospital in Toronto, Ontario, Canada and shows how this program exemplifies the medicalization of deafness while denying deaf children the opportunity to learn sign language. Using Foucault's concept of governmentality, the relations between power, knowledge, truth and their influences on the program's practices are revealed in order to provide insight into Canadian society's conceptions of deafness. This analysis reveals the Cochlear Implant Program as a capitalist establishment that is supported by unquestioned reverence of modern medicine and technology, oriented by a quest for normalcy. The paper concludes by encouraging members of the Deaf community and their supporters to challenge the hegemony of normalcy by utilizing alternate research-based knowledge-truths of cochlear implants and sign language.